Double Intervention in A Patient with Large Patent Ductus Arteriosus and Moderate Upper Muscular Ventricular Septal Defect with Bidirectional Shunt with Severe Pulmonary Hypertension - Nurun Nahar Fatema; Das, Priyanka (Cardiovascular Journal, 2024)
Patent ductus arteriosus (PDA) and Ventricular septal defect (VSD) are commonly encountered problems and constitute about 40% of all congenital heart lesions. The association of these two conditions in a single patient is not very uncommon. Both these conditions can be treated by placing intracardiac devices. Double interventional closure of PDA and VSD was performed in a gravely ill infant at her 3 months and 5 months of age respectively, who was suffering from recurrent pneumonia and heart failure since birth. These were lifesaving procedure for that patient which led to writing this report. Cardiovasc j 2024; 16(2): 105-109